Prevalence of obesity and severe obesity in US children, 1999‐2014. Issue 5 (May 2016) - Skinner, Asheley Cockrell; Perrin, Eliana M.; Skelton, Joseph A.
Abstract : Objective: Provide the most recent data on the prevalence of obesity and severe obesity among United States children and adolescents aged 2 to 19 years. Methods: The National Health and Nutrition Examination Survey, 1999–2014, was used. Weight status was defined using measured height and weight and standard definitions as follows: overweight as ≥85th percentile for age‐ and sex‐specific BMI; class I obesity as ≥95th percentile; class II obesity as ≥120 of the 95th percentile, or BMI ≥35; and class III obesity as ≥140% of the 95th percentile, or BMI ≥40. This study reports the prevalence of obesity by 2‐year National Health and Nutrition Examination Survey cycle and Wald tests comparing the 2011–2012 cycle with the 2013–2014 cycle, as well as the linear trend from 1999 to 2014. Multivariable logistic regression models estimated odds ratios for differences by each 2‐year cycle. Results: In 2013–2014, 17.4% of children met criteria for class I obesity, including 6.3% for class II and 2.4% for class III, none statistically different than 2011–2012. A clear, statistically significant increase in all classes of obesity continued from 1999 through 2014. Conclusions: There is no evidence of a decline in obesity prevalence in any age group, despite substantial clinical and policy efforts targeting the issue.